Material Experience: Kebaruan Dalam Desain Yang Berfokus Pada Material Studi Kasus: Desain Aksesori Fashion Berbasis Material Polyvinyl Chloride (PVC) - John Martono; Eka Arifianty Puspita (JURNAL RUPA, 2022)
Material selection is indubitably prominent in design creation. Technical and physical properties of a material are highly considered to determine function, utility, and manufacturing process. However, material selection is not only pivotal to design but also central to the users. Users have their own experiences with material that constructs their perception, association, and definition of materials. In fashion, the material experiences influence consumers’ purchasing decisions. Fashion consumers begin their reasoning with material thinking and interaction (if possible). The hands-on interaction of the product, where the material is implemented, stimulates memories that help their consuming decisions. Prior researches also argued that integration of material experiences in design will optimize outcomes, specifically providing user satisfaction. Those arguments inspired this research to investigate material experience in the design process. Experiences of material polyvinylchloride were observed by adopting the Material Driven Design method and the material experience’s pattern were illustrated by utilizing the Meaning of Material model. According to the research done in the Do-It-Yourself approach, material experiences were identified and seen transforming in every step of the process. Furthermore, the study of material experience was found beneficial for helping designers in understanding and measuring the intangible success of product, specifically user satisfaction.